Comparison of self-care in non-cardiac diabetic patients - Asghari F (Dove Medical Press, 2019)
Fatemeh Asghari,1 Monir Nobahar1–31Faculty of Nursing and Midwifery, Semnan University of Medical Sciences, Semnan, Iran; 2Nursing Care Research Center, Faculty of Nursing and Midwifery, Semnan University of Medical Sciences, Semnan, Iran; 3Social Determinants of Health Research Center, Semnan University of Medical Sciences, Semnan, IranCorrespondence: Monir NobaharNursing Care Research Center, Faculty of Nursing and Midwifery, Semnan University of Medical Sciences, Semnan, IranTel +98 2 333 654 190Fax +98 2 333 654 209Email Nobahar43@Semums.ac.irBackground: In general, the majority of diabetic patients suffering from a lack of capability in controlling different aspects of self-care have likely been prone to cardiovascular disease. To reduce the economic burden in societies and the rate of death on one hand, and improve life expectancy, on the other hand, it seems necessary to emphasize self-care training in diabetic patients. The purpose of this study was to determine comparison of self-care in cardiac and non-cardiac diabetic patients.Methods: This descriptive-analytic study was carried out with 136 diabetic participants selected using random sampling and divided into two groups of 68 non-cardiac diabetic patients. Data were collected using a demographic and diabetic patient’s self-management questionnaire (DSMQ). For the analysis of the data, SPSS16 was employed to check the significance test at the level of P<0.05.Results: In this study, twenty-eight (41.2%) and forty (58.8%) of the participants in each group were male and female, respectively. Their ages spanned from (61.35±13.34) in non-cardiac diabetic group to (65.94±8.74) in cardiac diabetic participants. There were significant differences between two groups, specifically in patients with cardiac diabetic disease in different aspects, for instance, including glucose monitoring (F=4.977, P=0.027, η2,=0.036), diet control (F=9.125, P=0.003, η2,=0.064), physical activity (F=22.954, P=0.0001, η2,=0.146) and health care awareness (F=31.366, P=0.0001, η2,=0.19).Conclusion: According to DSMQ questionnaire in the present study, glucose monitoring, diet control, physical activity, and health care awareness in diabetic patients with heart disease were significantly reported to have been better than the other group with no cardiac problem. Due to insufficient self-care in diabetic patients and some consequences such as poor health, heart disease as one of the complications of diabetes, hospital re-admission and heavy costs, the therapeutic team should be alerted to self-care training.Keywords: type II diabetes, self-care, heart disease